Association Between Hypertensive Disorders of Pregnancy and Later Risk of Cardiomyopathy. Issue 7 (July 2016) - Behrens, Ida; Basit, Saima; Lykke, Jacob Alexander; Ranthe, Mattis Flyvholm; Wohlfahrt, Jan; Bundgaard, Henning; Melbye, Mads; Boyd, Heather A.
Abstract : (Abstracted from JAMA 2016;315(10):1026–1033) Hypertensive disorders of pregnancy (HDP), which include preeclampsia and gestational hypertension, are characterized by de novo hypertension, with or without abnormal biochemical findings, in the second half of pregnancy and occur in up to 10% of pregnancies worldwide. The aim of this study was to investigate the association between HDP and cardiomyopathy after the peripartum period.